Polynaphthyl ester resin and preparation method thereof
By using three-stage gradient heating reaction and strong shear continuous polymerization technology in the preparation process of polynaphthalate resin, the problem of high dielectric constant and dielectric loss at high frequency is solved, and dielectric is realized Optimization of performance and improvement of production efficiency.
Patent Information
- Application Number
- CN202411754161.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing polynaphthalene resin has high dielectric constant and dielectric loss at high frequencies, which is difficult to meet the needs of future 6G communications. At the same time, there are poor heat and mass transfer capabilities and thermal oxygen degradation problems during its preparation process.
The three-stage gradient temperature-raising reaction is used to obtain low-molecular weight prepolymers, and further react in a continuous polymerization equipment with strong shearing effect to increase the molecular weight, thereby preparing all-aryl fluoropolynaphthalene with high molecular weight and excellent dielectric properties Resin.
The dielectric constant and dielectric loss of polynaphthalate resin are reduced, which improves its performance at high frequencies, solves the problems of poor heat and mass transfer ability and thermal oxygen degradation, and improves the degree of continuous production and efficiency.
Smart Images

Figure BDA0005165825410000031 
Figure BDA0005165825410000041 
Figure BDA0005165825410000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polynaphthyl ester resin with excellent dielectric properties and a preparation method thereof. Background Art
[0002] Polynaphthyl ester, as a high-performance polymer material with naphthalene ring as the skeleton structure, has a significantly increased main chain rigidity due to the naphthalene ring structure on the molecular chain, which makes it have excellent mechanical properties, thermal properties, barrier properties and radiation resistance. After heating to a certain temperature, it exhibits liquid crystal properties. The rigid molecular structure makes it difficult for the dipole to undergo orientation movement under an alternating electric field, so it has low dielectric loss, and this low loss performance advantage is particularly obvious at high frequencies. However, its dielectric constant at high frequencies is around 3-3.5. In order to meet the application needs of 6G in the future, it is necessary to further reduce its dielectric constant and dielectric loss at high frequencies. However, fully aromatic polynaphthyl ester is usually prepared by melt polymerization. In the later stage of the reaction, a high temperature and high vacuum environment is required to further increase the molecular weight, which will lead to problems such as poor heat and mass transfer capacity and ultimately cause the problem of thermal oxidation degradation of polynaphthyl ester. The main way to solve this problem is to design the molecular structure and improve the polymerization process to develop polynaphthyl ester resins with excellent high dielectric properties suitable for the 6G information age. Among them, fully aromatic polynaphthyl ester resins with excellent high dielectric properties are fundamental.
[0003] At present, the preparation routes of polynaphthyl ester resin include direct esterification and transesterification. The direct esterification method is similar to the reaction of PET, but due to the presence of naphthalene rings, the steric hindrance effect is increased, so the reaction conditions are extremely harsh and the purity of the monomer is high. There are no industrialized products at present. The transesterification method is currently the most widely used method in industry. The process is divided into two parts. The first is melt transesterification. In the later stage of this stage, the high molecular weight leads to high melt viscosity, mass transfer and heat transfer problems, which can easily cause uneven molecular weight distribution, and even carbonization increases impurities and poor batch stability; the second is solid phase polycondensation, which further increases the molecular weight of polynaphthyl ester. However, the increase in molecular weight requires higher temperature and high vacuum conditions, which has higher requirements on equipment, and the reaction time is long, up to dozens of hours. The disadvantage of long cycle is self-evident.
[0004] Obviously, the polynaphthyl ester currently prepared by traditional methods cannot meet the needs of future 6G communications. Summary of the invention
[0005] The invention provides a preparation method of polynaphthyl ester, comprising the following steps: reacting p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, raw material A, a catalyst and an antioxidant at 200-220 DEG C in an inert atmosphere, continuing to heat to 240-280 DEG C for reaction, and then heating to 300-360 DEG C for reaction, discharging, crushing and drying to obtain a prepolymer; and continuously polymerizing the prepolymer at 300-340 DEG C under vacuum to obtain the polynaphthyl ester; wherein the raw material A is raw material B or raw material C, the raw material B is fluorine-containing acetoxybenzoic acid, and the raw material C is aromatic diacid and fluorine-containing aromatic diacetylamide.
[0006] Specifically, in the preparation method of the polynaphthyl ester, the p-acetoxybenzoic acid is obtained by acetylation of p-hydroxybenzoic acid with acetic anhydride.
[0007] Specifically, in the preparation method of the above polynaphthyl ester, the 6-acetoxy-2-naphthoic acid is obtained by acetylation of 6-hydroxy-2-naphthoic acid with acetic anhydride.
[0008] Preferably, in the preparation method of the above polynaphthyl ester, the raw material B is selected from p-acetoxybenzoic acid containing fluorine at the 2nd and / or 6th positions, m-acetoxybenzoic acid containing fluorine at the 2nd and / or 3rd positions, and o-acetoxybenzoic acid containing fluorine at the 2nd position.
[0009] Specifically, in the preparation method of the polynaphthyl ester, the fluorinated p-acetoxybenzoic acid is obtained by acetylation of fluorinated p-hydroxybenzoic acid with acetic anhydride.
[0010] Specifically, in the preparation method of the polynaphthyl ester, the fluorinated m-acetoxybenzoic acid is obtained by acetylation of fluorinated m-hydroxybenzoic acid with acetic anhydride.
[0011] Specifically, in the preparation method of the polynaphthyl ester, the fluorinated o-acetoxybenzoic acid is obtained by acetylation of fluorinated o-hydroxybenzoic acid with acetic anhydride.
[0012] Furthermore, in the above-mentioned preparation method of polynaphthyl ester, the raw material B is selected from one or more of 2-fluoro-4-acetoxybenzoic acid, 2-fluoro-5-acetoxybenzoic acid, 2-fluoro-6-acetoxybenzoic acid, 3-fluoro-5-acetoxybenzoic acid, 2,6-difluoro-4-acetoxybenzoic acid, and 4-acetoxy-2-trifluoromethylbenzoic acid.
[0013] Specifically, in the preparation method of the polynaphthyl ester, the aromatic diacid is selected from one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, and 2,6-naphthalene dicarboxylic acid.
[0014] Specifically, in the preparation method of the above-mentioned polynaphthyl ester, the fluorine-containing aromatic diacetylamide is selected from one or more of 1,4-diacetylamino-2,5-difluorobenzene, 2,3,5,6-tetrafluoro-1,4-benzene diacetylamide, 4,4'-diacetylamino-2,2'-difluorobiphenyl, 4,4'-diacetylamino-2,2',6,6'-tetrafluorobiphenyl, 4,4'-diacetylaminooctafluorobiphenyl, 1,2-bis(4-acetylaminophenoxy)hexafluorocyclobutane, 4,4'-(hexafluoroisopropyl)diphenylacetylamide, and 2,2-bis(trifluoromethyl)diacetylaminobiphenyl.
[0015] Specifically, in the preparation method of the above-mentioned polynaphthyl ester, the catalyst is selected from titanium dioxide, titanium glycol, titanium acetylacetonate, n-butyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannic acid, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, and zinc lactate. One or more.
[0016] Specifically, in the preparation method of the above polynaphthyl ester, the antioxidant is selected from one or more of antioxidant BHT, antioxidant 1010, antioxidant 168, triphenyl phosphite, and dilauryl thiodipropionate.
[0017] Preferably, in the above-mentioned preparation method of polynaphthyl ester, when raw material A is selected from raw material B, the addition amount of p-acetoxybenzoic acid is 40-80%, the addition amount of 6-acetoxy-2-naphthoic acid is 10-40%, and the addition amount of raw material B is 5-30% by mole percentage.
[0018] Preferably, in the above-mentioned preparation method of polynaphthyl ester, when raw material A selects raw material C, the addition amount of acetoxybenzoic acid is 40-80% by mole percentage, the addition amount of 6-acetoxy-2-naphthoic acid is 10-40%, the addition amount of aromatic diacid is 5-15%, and the addition amount of fluorinated aromatic diacetylamide is 5-15%.
[0019] More preferably, in the above method for preparing polynaphthyl ester, the molar ratio of the aromatic diacid to the fluorine-containing aromatic diacetylamide is 1:1.
[0020] Preferably, in the above-mentioned method for preparing polynaphthyl ester, the added amount of the catalyst is 40 to 450 ppm based on the total weight of acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid and raw material A.
[0021] Preferably, in the above-mentioned method for preparing polynaphthyl ester, the added amount of the antioxidant is 0.05-0.5% of the total weight of acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid and raw material A.
[0022] Specifically, in the preparation method of the polynaphthyl ester, the reaction is carried out in a Hastelloy polymerization reactor.
[0023] Specifically, in the above-mentioned method for preparing polynaphthyl ester, the inert atmosphere is nitrogen.
[0024] Specifically, in the above-mentioned preparation method of polynaphthyl ester, the reaction is carried out at 200-220° C. for 1.5-3 hours.
[0025] Specifically, in the preparation method of the polynaphthyl ester, the reaction is carried out at 240-280° C. for 2-3 hours.
[0026] Specifically, in the preparation method of the polynaphthyl ester, the reaction is carried out at 300-360° C. for 0.1-3 h.
[0027] Specifically, in the above-mentioned method for preparing polynaphthyl ester, the continuous polymerization reaction is carried out in a continuous polymerization device.
[0028] Specifically, in the preparation method of the polynaphthyl ester, the reaction is carried out at 300-340° C. for 5-30 minutes.
[0029] Specifically, in the above-mentioned method for preparing polynaphthyl ester, the vacuum degree of the vacuum is 0.08-0.1 MPa.
[0030] Specifically, in the above-mentioned preparation method of polynaphthyl ester, the shear rate is controlled to be 50-200s during the continuous polymerization reaction. -1 .
[0031] The present invention also provides polynaphthyl ester prepared by the preparation method of polynaphthyl ester.
[0032] Furthermore, the above polynaphthyl ester has a structural formula as shown in formula (I):
[0033]
[0034] Furthermore, the above-mentioned polynaphthyl ester, based on the total mole of the repeating structural units, has a mole fraction (n1) of the benzene ring repeating structural units of 40-80 mol%, a mole fraction (n3) of the naphthalene ring repeating structural units of 10-40 mol%, and a mole fraction (n2) of the benzene ring portion substituted with fluorine atoms of 5-30 mol%.
[0035] Furthermore, the above-mentioned polynaphthyl ester, based on the total mole of the repeating structural units, has a mole fraction (n1) of the benzene ring repeating structural units of 45-70 mol%, a mole fraction (n3) of the naphthalene ring repeating structural units of 20-40 mol%, and a mole fraction (n2) of the benzene ring portion substituted with fluorine atoms of 10-30 mol%.
[0036] Furthermore, the above polynaphthyl ester has a structural formula as shown in formula (II):
[0037]
[0038] Furthermore, the above-mentioned polynaphthyl ester, based on the total mole of the repeating structural units, has a mole fraction (n1) of the benzene ring repeating structural unit of 40-80 mol%, a mole fraction (n2) of the naphthalene ring repeating structural unit of 10-40 mol%, and an equal mole fraction of the aromatic diacid structural unit (Ar1) and a mole fraction of the fluorine-substituted aromatic diamine structural unit (Ar2), both of which are 5-15 mol%.
[0039] Furthermore, the above-mentioned polynaphthyl ester, based on the total mole of the repeating structural units, has a mole fraction (n1) of the benzene ring repeating structural unit of 45-70 mol%, a mole fraction (n2) of the naphthalene ring repeating structural unit of 20-40 mol%, and an equal mole fraction of the aromatic diacid structural unit (Ar1) and a mole fraction of the fluorine-substituted aromatic diamine structural unit (Ar2), both of which are 2.5-12.5 mol%.
[0040] The invention adopts a three-stage gradient temperature rise reaction to obtain a low molecular weight prepolymer, and then reacts in a continuous polymerization device with a strong shearing effect to further increase the molecular weight, thereby obtaining a wholly aromatic polynaphthyl ester resin with a high molecular weight and excellent dielectric properties. The production has a high degree of continuity, a short cycle and high efficiency, and the polynaphthyl ester resin can be used in microelectronic devices. DETAILED DESCRIPTION
[0041] The invention provides a method for preparing polynaphthyl ester. The method for preparing polynaphthyl ester comprises the following steps: adding p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, raw material A, a catalyst and an antioxidant into a Hastelloy polymerization kettle, introducing an inert gas such as nitrogen, closing the reflux and discharging small molecular acetic acid after reflux reaction at 200-220°C for 1.5-3h, continuing to raise the temperature to 240-280°C for reaction for 2-3h, then raising the temperature to 300-360°C for reaction for 0.1-3h, discharging through the Hastelloy polymerization kettle, crushing and drying to obtain a prepolymer; then reacting at 300-340°C for 5-30min in a continuous polymerization device with strong shearing action, wherein the vacuum degree is 0.08-0.1MPa and the shear rate is 50-200s -1, obtaining a high molecular weight fluorinated polynaphthyl ester resin with excellent dielectric properties; wherein the raw material A is raw material B or raw material C, the raw material B is fluorinated acetoxybenzoic acid, and the raw material C is aromatic diacid and fluorinated aromatic diacetylamide.
[0042] In the present invention, p-acetoxybenzoic acid can be purchased directly or obtained by acetylation of p-hydroxybenzoic acid. The acetylation reaction is a conventional method in the art. The molar ratio of acetic anhydride to p-hydroxybenzoic acid is 1.5 to 3:1. Preferably, it is 1.5 times. Acetic anhydride and p-hydroxybenzoic acid are maintained at 100-140° C. for 2-4 hours to complete the acetylation of the phenolic hydroxyl group to obtain p-acetoxybenzoic acid.
[0043] In the present invention, 6-acetoxy-2-naphthoic acid can be purchased directly, or it can be obtained by acetylation of 6-hydroxy-2-naphthoic acid. The acetylation reaction is a conventional method in the art. The molar ratio of acetic anhydride to 6-hydroxy-2-naphthoic acid is 1.5 to 3:1. Preferably, it is 1.5 times. Acetic anhydride and 6-hydroxy-2-naphthoic acid are maintained at 100-140° C. for 2-4 hours to complete the acetylation of the phenolic hydroxyl group to obtain 6-acetoxy-2-naphthoic acid.
[0044] In the present invention, the raw material B containing fluorine acetoxybenzoic acid can be obtained by acetylation of the corresponding raw material. Raw material B is selected from one or more of 2-fluoro-4-acetoxybenzoic acid, 2-fluoro-5-acetoxybenzoic acid, 2-fluoro-6-acetoxybenzoic acid, 3-fluoro-5-acetoxybenzoic acid, 2,6-difluoro-4-acetoxybenzoic acid, and 4-acetoxy-2-trifluoromethylbenzoic acid. Further, the raw material B is selected from 2-fluoro-4-hydroxybenzoic acid (structural formula: ), 2-fluoro-5-hydroxybenzoic acid (structural formula is ), 2-fluoro-6-hydroxybenzoic acid (structural formula is ), 3-fluoro-5-hydroxybenzoic acid (structural formula: ), 2,6-difluoro-4-hydroxybenzoic acid (structural formula is ), 4-hydroxy-2-trifluoromethylbenzoic acid (structural formula: ) is used as a raw material and one or more of them are acetylated with acetic anhydride. The acetylation reaction is a conventional method in the art. The molar ratio of acetic anhydride to the above raw materials is 1.5 to 3:1. Preferably, it is 1.5 times. Acetic anhydride and the above raw materials are kept at 100-140° C. for 2-4 hours to complete the acetylation of the phenolic hydroxyl group to obtain raw material B.
[0045] In the present invention, the aromatic diacid is selected from terephthalic acid (structural formula: ), isophthalic acid (structural formula is )、4,4'-biphenyldicarboxylic acid (structural formula is )、2,7-naphthalene dicarboxylic acid (structural formula is )、2,6-naphthalene dicarboxylic acid (structural formula is )
[0046] In the present invention, the fluorine-containing aromatic diacetylamide can be obtained by acetylation of the corresponding raw materials. The fluorine-containing aromatic diacetylamide is selected from one or more of 1,4-diacetylamino-2,5-difluorobenzene, 2,3,5,6-tetrafluoro-1,4-benzene diacetylamide, 4,4'-diacetylamino-2,2'-difluorobiphenyl, 4,4'-diacetylamino-2,2',6,6'-tetrafluorobiphenyl, 4,4'-diacetylaminooctafluorobiphenyl, 1,2-bis(4-acetylaminophenoxy)hexafluorocyclobutane, 4,4'-(hexafluoroisopropylidene)diphenylacetylamide, and 2,2-bis(trifluoromethyl)diacetylaminobiphenyl. The fluorine-containing aromatic diacetylamide is selected from one or more of 1,4-diamino-2,5-difluorobenzene (structural formula: )、2,3,5,6-tetrafluoro-1,4-phenylenediamine (structural formula is )、4,4'-diamino-2,2'-difluorobiphenyl (structural formula is )、4,4'-diamino-2,2',6,6'-tetrafluorobiphenyl (structural formula is ), 4,4'-diaminooctafluorobiphenyl (structural formula: )、1,2-bis(4-aminophenoxy)hexafluorocyclobutane (structural formula 4,4'-(Hexafluoroisopropylidene)diphenylamine (structural formula: )、2,2-bis(trifluoromethyl)diaminobiphenyl (structural formula is ) is used as a raw material and one or more of them are acetylated with acetic anhydride. The acetylation reaction is a conventional method in the art. The molar ratio of acetic anhydride to the above raw materials is 1.5 to 3:1. Preferably, it is 3 times. Acetic anhydride and the above raw materials are kept at 100-140° C. for 2-4 hours to complete the acetylation of the amino group to obtain fluorine-containing aromatic diacetylamide.
[0047] In the present invention, when the aromatic diacid is 4,4'-biphenyldicarboxylic acid, the fluorine-containing aromatic diethylamide is not 4,4'-diacetylaminooctafluorobiphenyl.
[0048] Example 1
[0049] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 98.8% and a yield of 96%.
[0050] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 120° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash and filter with water for more than 3 times, and dry at 140° C. for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% and a yield of 95%.
[0051] 174.1 g (1 mol) of 2,6-difluoro-4-hydroxybenzoic acid and 153.1 g (1.5 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120° C. for 3 h to obtain a 2,6-difluoro-4-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 2,6-difluoro-4-acetoxybenzoic acid with a purity of 98.9% and a yield of 89%.
[0052] 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 108 g (0.5 mol, 10 mol%) of purified 2,6-difluoro-4-acetoxybenzoic acid, 80 ppm of catalyst magnesium acetate and 0.1 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 220° C. and refluxed for 2 h to discharge small molecular acetic acid, and then the temperature was raised to 250° C. and reacted for 2 h, and the temperature was further raised to 320° C. and reacted for 0.5 h before discharging, and a prepolymer was obtained after crushing and drying; the prepolymer was added into a continuous polymerization device, and the reaction was carried out at a temperature of 320° C., a vacuum degree of 0.09 MPa and a shear rate of 120 s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a high molecular weight fully aromatic fluorinated polynaphthyl ester resin with a yield of about 86%.
[0053] Pentafluorophenol was used to prepare a 0.1g / dL solution. At 60°C, the characteristic viscosity was measured by an Ubbelohde viscometer to be 4.6, indicating that it has a relatively high molecular weight. The thermal properties were measured by DSC and TGA, and the melting point was 280°C, the thermal decomposition temperature was 510°C, and the residual carbon content at 800°C was 45.1%, indicating good heat resistance. The viscosity was 320Pa.s at 300°C and 1Hz tested by a flat plate rheometer, and it showed a more obvious shear thinning phenomenon, indicating that the resin has excellent fluidity. The tensile strength was 181MPa and the tensile modulus was 7.2GPa, indicating excellent mechanical properties. The water absorption rate after immersion in water for 24 hours was only 0.02%, the dielectric constant was 2.46 at 20GHz, and the dielectric loss was 0.0020. The prepared fully aromatic fluorinated polynaphthyl ester resin can be used in microelectronic devices.
[0054]
[0055] Example 2
[0056] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 98.8% and a yield of 96%.
[0057] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 120° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash and filter with water for more than 3 times, and dry at 140° C. for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% and a yield of 95%.
[0058] 156.1 g (1 mol) of 2-fluoro-4-hydroxybenzoic acid and 153.14 g (1.5 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 130° C. for 3 h to obtain a 2-fluoro-4-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 2-fluoro-4-acetoxybenzoic acid with a purity of 98.6% and a yield of 63%.
[0059] 495.44 g (2.75 mol, 55 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 198.15 g (1 mol, 20 mol%) of purified 2-fluoro-4-acetoxybenzoic acid, 80 ppm of catalyst manganese acetate and 0.1 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 220° C. and refluxed for 2 h to discharge small molecular acetic acid, and then the temperature was raised to 250° C. and reacted for 2 h, and then the temperature was raised to 320° C. and reacted for 0.5 h before discharging, and the prepolymer was obtained by crushing and drying; the prepolymer was added into a continuous polymerization device, and the reaction was carried out at a temperature of 320° C., a vacuum degree of 0.09 MPa and a shear rate of 120 s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a high molecular weight wholly aromatic fluorinated polynaphthyl ester resin with a yield of about 83%.
[0060] Pentafluorophenol was used to prepare a 0.1g / dL solution. At 60°C, the characteristic viscosity was measured by an Ubbelohde viscometer to be 4.3, indicating that it has a relatively high molecular weight. The thermal properties were measured by DSC and TGA, and the melting point was 276°C, the thermal decomposition temperature was 512°C, and the residual carbon content at 800°C was 45.23%, indicating good heat resistance. The viscosity was 390Pa.s at 300°C and 1Hz tested by a flat plate rheometer, and it showed a more obvious shear thinning phenomenon, indicating that the resin has excellent fluidity. The tensile strength was 190MPa and the tensile modulus was 7.2GPa, indicating excellent mechanical properties. The water absorption after 24h was only 0.04%, the dielectric constant at 20GHz was 2.58, and the dielectric loss was 0.0022. The prepared fully aromatic fluorinated polynaphthyl ester resin can be used in microelectronic devices.
[0061]
[0062] Example 3
[0063] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 97.5% and a yield of 92%.
[0064] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 135 ° C for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140 ° C for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 96.8% and a yield of 95%.
[0065] 206.1 g (1 mol) of 4-hydroxy-2-trifluoromethylbenzoic acid and 153.1 g (1.5 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133° C. for 3 h to obtain a 4-acetoxy-2-trifluoromethylbenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4-acetoxy-2-trifluoromethylbenzoic acid with a purity of 98.5% and a yield of 96%.
[0066] 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 124.08 g (0.5 mol, 10 mol%) of purified 4-acetoxy-2-trifluoromethylbenzoic acid, 90 ppm of catalyst zinc acetate and 0.2 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 210° C., refluxed for 2 h, and then the reflux was closed and the small molecular acetic acid was discharged, and then the temperature was raised to 250° C. for 2 h, and the temperature was further raised to 320° C. for 0.5 h, and then the material was discharged, and a prepolymer was obtained by crushing and drying; the prepolymer was added into a continuous polymerization device, and the reaction was carried out at a temperature of 315° C., a vacuum degree of 0.09 MPa and a shear rate of 120 s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a high molecular weight fully aromatic fluorinated polynaphthyl ester resin with a yield of about 86%.
[0067] Pentafluorophenol was used to prepare a 0.1g / dL solution. At 60°C, the characteristic viscosity was measured by an Ubbelohde viscometer to be 3.9. The thermal properties were measured by DSC and TGA. The melting point was 270°C, the thermal decomposition temperature was 515°C, and the residual carbon content at 800°C was 45.6%, which showed good heat resistance. The viscosity was 460Pa.s at 300°C and 1Hz tested by a flat plate rheometer, and it showed a more obvious shear thinning phenomenon, indicating that the resin had excellent fluidity. The tensile strength was 150MPa and the tensile modulus was 6.5GPa. The water absorption after immersion in water for 24 hours was only 0.06%. The dielectric constant at 20GHz was 2.43 and the dielectric loss was 0.0030. The prepared fully aromatic fluorinated polynaphthyl ester resin can be used in microelectronic devices.
[0068]
[0069] Example 4
[0070] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 140° C. for 3 h to obtain a p-acetoxybenzoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 98.8% and a yield of 96%.
[0071] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 140° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140° C. for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% and a yield of 95%.
[0072] 1561.1 g (10 mol) of 3-fluoro-5-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 140° C. for 3 h to obtain a 3-fluoro-5-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 2-fluoro-4-acetoxybenzoic acid with a purity of 98 and a yield of 60%.
[0073] 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 99.08 g (0.5 mol, 10 mol%) of purified 3-fluoro-5-acetoxybenzoic acid, 80 ppm of catalyst lithium acetate and 0.1 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 220° C. and refluxed for 2 h, then the reflux was closed and the small molecular acetic acid was discharged, and then the temperature was raised to 260° C. and reacted for 2 h, and the temperature was further raised to 320° C. and reacted for 0.5 h before discharging, and the prepolymer was obtained by crushing and drying; the prepolymer was added into a continuous polymerization device, and the reaction was carried out at a temperature of 320° C., a vacuum degree of 0.09 MPa and a shear rate of 120 s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a high molecular weight wholly aromatic fluorinated polynaphthyl ester resin with a yield of about 82%.
[0074] Pentafluorophenol was used to prepare a 0.1g / dL solution. At 60°C, the characteristic viscosity was measured by an Ubbelohde viscometer to be 4.6, indicating that it has a relatively high molecular weight. The thermal properties were measured by DSC and TGA, and the melting point was 263°C, the thermal decomposition temperature was 479°C, and the residual carbon content at 800°C was 40.23%, indicating good heat resistance. The viscosity was 590Pa.s at 300°C and 1Hz as tested by a flat plate rheometer. The tensile strength was 166MPa and the tensile modulus was 6.1GPa, indicating excellent mechanical properties. The water absorption after 24h was 0.08%, the dielectric constant at 20GHz was 2.69, and the dielectric loss was 0.0038. The prepared fully aromatic fluorinated polynaphthyl ester resin can be used in microelectronic devices.
[0075]
[0076] Example 5
[0077] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 98.8% and a yield of 96%.
[0078] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 120° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash and filter with water for more than 3 times, and dry at 140° C. for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% and a yield of 95%.
[0079] 328.17 g (1 mol) of 4,4'-diaminooctafluorobiphenyl and 306.3 g (3 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120° C. for 3 h to obtain a 4,4'-diacetylaminooctafluorobiphenyl solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4,4'-diacetylaminooctafluorobiphenyl with a purity of 97.3% and a yield of 78%.
[0080] Weigh 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 41.53 g (0.25 mol, 5 mol%) of terephthalic acid, 103.06 g (0.25 mol, 5 mol%) of purified 4,4'-diacetylaminooctafluorobiphenyl, 80 ppm of catalyst magnesium acetate and 0.1 wt% of anti- The oxidant 1010 was added into a 5L reactor equipped with mechanical stirring, a reflux condenser and a vacuum reactor, and then nitrogen was introduced. The temperature was raised to 220°C and the reaction was refluxed for 2 hours, after which the reflux was closed and the small molecular weight acetic acid was discharged. The temperature was then raised to 260°C and the reaction was continued to be raised to 320°C for 1 hour before the material was discharged. The prepolymer was crushed and dried to obtain the prepolymer. The prepolymer was added into a continuous polymerization device and heated at a temperature of 320°C, a vacuum degree of 0.09 MPa and a shear rate of 120 s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a high molecular weight fully aromatic fluorinated polynaphthyl ester resin with a yield of about 80%.
[0081] The solution of 0.1g / dL was prepared with pentafluorophenol. The characteristic viscosity was 5.3 at 60℃ using an Ubbelohde viscometer, indicating that it has a high molecular weight. The thermal performance data measured by DSC and TGA showed that the melting point can reach 300℃, the thermal decomposition temperature can reach 508℃, and the residual carbon content at 800℃ is 43%, which has good heat resistance. The viscosity at 300℃ and 1Hz tested by a flat plate rheometer is 598Pa.s, and it shows a more obvious shear thinning phenomenon, indicating that the resin has excellent fluidity. The tensile strength is 163MPa and the tensile modulus is 5.8GPa, which has excellent mechanical properties. The water absorption rate after immersion in water for 24h is only 0.08%, the dielectric constant at 20GHz is 2.58, and the dielectric loss is 0.0035. The prepared fully aromatic fluorinated polynaphthyl ester resin can be used in microelectronic devices.
[0082]
[0083] Comparative Example 1
[0084] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 97.5% and a yield of 92%.
[0085] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 135 ° C for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140 ° C for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 96.8% and a yield of 95%.
[0086] 206.1 g (1 mol) of 4-hydroxy-2-trifluoromethylbenzoic acid and 153.1 g (1.5 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133° C. for 3 h to obtain a 4-acetoxy-2-trifluoromethylbenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4-acetoxy-2-trifluoromethylbenzoic acid with a purity of 98.5% and a yield of 96%.
[0087] 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 124.08 g (0.5 mol, 10 mol%) of purified 4-acetoxy-2-trifluoromethylbenzoic acid, 100 ppm of catalyst magnesium acetate and 0.1 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced. The temperature was raised to 230° C. and refluxed for 2 h, then the reflux was closed and the small molecular acetic acid was discharged, and then the temperature was raised to 260° C. and reacted for 2 h. The temperature was further raised to 320° C. and reacted under vacuum for 1.5 h, then nitrogen was filled into the reaction kettle, the temperature was lowered and the material was discharged, and the fully aromatic fluorinated polynaphthyl ester resin was obtained by crushing and drying.
[0088] Pentafluorophenol was used to prepare a 0.1 g / dL solution. At 60°C, the characteristic viscosity was measured by an Ubbelohde viscometer to be 0.9, and the molecular weight was low. The thermal properties were measured by DSC and TGA, with a melting point of 268°C and a thermal decomposition temperature of 450°C. The tensile strength was 52 MPa and the tensile modulus was 2.1 GPa, indicating poor mechanical properties. The dielectric constant at 20 GHz was 3.2 and the dielectric loss was 0.012, indicating poor dielectric properties. The prepared fully aromatic fluorinated polynaphthyl ester resin cannot be used in microelectronic devices.
[0089]
[0090] Comparative Example 2
[0091] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 140° C. for 3 h to obtain a p-acetoxybenzoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 98.8% and a yield of 96%.
[0092] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 140° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140° C. for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% and a yield of 95%.
[0093] 210.08 g (1 mol) of 2,3,5,6-tetrafluoro-4-hydroxybenzoic acid and 153.14 g (1.5 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 140° C. for 3 h to obtain a 2,3,5,6-tetrafluoro-4-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4-acetoxy-tetrafluorobenzoic acid with a purity of 98.7 and a yield of 56%.
[0094] 585.5 g (3.25 mol, 65 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 128.05 g (0.5 mol, 10 mol%) of purified 2,3,5,6-tetrafluoro-4-acetoxybenzoic acid, 80 ppm of catalyst manganese acetate and 0.1 wt% of antioxidant 1010 were added into a 5 L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 200° C. and refluxed for 2 h to discharge small molecular acetic acid, and then the temperature was raised to 240° C. and reacted for 2 h, and the temperature was further raised to 300° C. and reacted for 1 h before discharging to obtain a black thermal oxidation degradation product. The prepared fully aromatic fluorinated polynaphthyl ester resin cannot be used in microelectronic devices.
[0095]
[0096] Comparative Example 3
[0097] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 97.5% and a yield of 92%.
[0098] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 135 ° C for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140 ° C for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 96.8% and a yield of 95%.
[0099] 328.17 g (1 mol) of 4,4'-diaminooctafluorobiphenyl and 306.3 g (3 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 120° C. for 3 h to obtain a 4,4'-diacetylaminooctafluorobiphenyl solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4,4'-diacetylaminooctafluorobiphenyl with a purity of 97.3% and a yield of 78%.
[0100] Weigh 585.5 g (2.75 mol, 55 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 121.12 g (0.5 mol, 10 mol%) of 4,4-biphenyldicarboxylic acid, 206.1 g (0.5 mol, 10 mol%) of purified 4,4'-diacetylaminooctafluorobiphenyl, 80 ppm of catalyst zinc acetate and 0.1 wt% antioxidant 1010 was added into a 5L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced, the temperature was raised to 220°C, reflux reaction was carried out for 2h, reflux was closed and small molecular acetic acid was discharged, and then the temperature was raised to 260°C for reaction for 2h, and the temperature was further raised to 320°C for 1h before discharging, and the prepolymer was obtained by crushing and drying; the above prepolymer was added into a continuous polymerization device, and the reaction was carried out at a temperature of 320°C, a vacuum degree of 0.09MPa and a shear rate of 120s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a fully aromatic fluorinated polynaphthyl ester resin with a yield of about 92%.
[0101] The solution of 0.1g / dL was prepared with pentafluorophenol. At 60℃, the intrinsic viscosity was measured by Ubbelohde viscometer to be 0.6, and the molecular weight was very low. The thermal performance data measured by DSC and TGA showed that the melting point was 340℃, the thermal decomposition temperature was 465℃, and the residual carbon content at 800℃ was 40%. The tensile strength was 35MPa, and the tensile modulus was 1.3GPa. The dielectric constant at 20GHz was 3.58, and the dielectric loss was 0.015. The prepared fully aromatic fluorinated polynaphthyl ester resin cannot be used in microelectronic devices due to its low molecular weight and poor dielectric properties.
[0102]
[0103] Comparative Example 4
[0104] 1380 g (10 mol) of p-hydroxybenzoic acid and 1531.4 g (15 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 133 ° C for 3 h to obtain a p-acetoxybenzoic acid solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140 ° C for 20 h to obtain purified p-acetoxybenzoic acid with a purity of 97.5% and a yield of 92%.
[0105] Weigh 1881.8 g (10 mol) of 6-hydroxy-2-naphthoic acid and 1531.4 g (15 mol) of acetic anhydride, add them into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and reflux at 135 ° C for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; pour the above solution into cold water, wash with water and filter for more than 3 times, and dry at 140 ° C for 20 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 96.8% and a yield of 95%.
[0106] 184.24 g (1 mol) of 4,4'-diaminobiphenyl and 306.3 g (3 mol) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 135° C. for 3 h to obtain a 4,4'-diacetylaminobiphenyl solution; the above solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 140° C. for 20 h to obtain purified 4,4'-diacetylaminobiphenyl with a purity of 97.8% and a yield of 87%.
[0107] Weigh 495.4 g (2.75 mol, 55 mol%) of purified p-acetoxybenzoic acid, 287.78 g (1.25 mol, 25 mol%) of purified 6-acetoxy-2-naphthoic acid, 83.07 g (0.5 mol, 10 mol%) of terephthalic acid, 134.16 g (0.5 mol, 10 mol%) of purified 4,4'-diacetylaminobiphenyl (1%-6%), 80 ppm of catalyst magnesium acetate and 0.1 wt% Antioxidant 1010 was added into a 5L Hastelloy reaction kettle with mechanical stirring and reflux condenser, and then nitrogen was introduced. The temperature was raised to 220°C for reflux reaction for 2h, and then the reflux was closed and the small molecular acetic acid was discharged. Then the temperature was raised to 260°C for reaction for 2h, and the temperature was further raised to 320°C for 1h before discharging. The fully aromatic fluorinated polynaphthyl ester resin was obtained by crushing and drying. The above prepolymer was added into a continuous polymerization device and precipitated at a temperature of 320°C, a vacuum degree of 0.09 MPa and a shear rate of 120s -1 The reaction was continued for 10 minutes, pelletized and dried to obtain a fully aromatic fluorinated polynaphthyl ester resin with a yield of about 87%.
[0108] The solution of 0.1g / dL was prepared with pentafluorophenol. The intrinsic viscosity was 2.9 at 60℃ using an Ubbelohde viscometer. The thermal properties were measured using DSC and TGA. The melting point was 320℃, the thermal decomposition temperature was 498℃, and the residual carbon content at 800℃ was 45%. The tensile strength was 160MPa, the tensile modulus was 6.3GPa, the dielectric constant was 3.5 at 20GHz, and the dielectric loss was 0.01. The prepared fully aromatic polynaphthyl ester resin cannot be used in microelectronic devices.
[0109]
Claims
1. A method for preparing polynaphthyl ester, characterized in that: The following steps are involved: The method comprises the following steps: reacting p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, raw material A, a catalyst and an antioxidant at 200-220° C. under an inert atmosphere, continuing to heat the reaction to 240-280° C., and then heating the reaction to 300-360° C., discharging, crushing and drying the prepolymer; and continuously polymerizing the prepolymer at 300-340° C. under vacuum to obtain the polynaphthyl ester; wherein the raw material A is raw material B or raw material C, the raw material B is fluorine-containing acetoxybenzoic acid, and the raw material C is aromatic diacid and fluorine-containing aromatic diacetylamide.
2. The method for preparing polynaphthyl ester according to claim 1, wherein: The raw material B is selected from p-acetoxybenzoic acid containing fluorine at the 2nd and / or 6th positions, m-acetoxybenzoic acid containing fluorine at the 2nd and / or 3rd positions, and o-acetoxybenzoic acid containing fluorine at the 2nd position; further, the raw material B is selected from one or more of 2-fluoro-4-acetoxybenzoic acid, 2-fluoro-5-acetoxybenzoic acid, 2-fluoro-6-acetoxybenzoic acid, 3-fluoro-5-acetoxybenzoic acid, 2,6-difluoro-4-acetoxybenzoic acid, and 4-acetoxy-2-trifluoromethylbenzoic acid.
3. The method for preparing polynaphthyl ester according to claim 1, wherein: The aromatic diacid is selected from one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, and 2,6-naphthalene dicarboxylic acid; the fluorine-containing aromatic diacetylamide is selected from one or more of 1,4-diacetylamino-2,5-difluorobenzene, 2,3,5,6-tetrafluoro-1,4-benzenediacetylamide, 4,4'-diacetylamino-2,2'-difluorobiphenyl, 4,4'-diacetylamino-2,2',6,6'-tetrafluorobiphenyl, 4,4'-diacetylaminooctafluorobiphenyl, 1,2-bis(4-acetylaminophenoxy)hexafluorocyclobutane, 4,4'-(hexafluoroisopropyl)diphenylacetylamide, and 2,2-bis(trifluoromethyl)diacetylaminobiphenyl.
4. The method for preparing a polynaphthyl ester according to any one of claims 1 to 3, wherein: When raw material A selects raw material B, the added amount of p-acetoxybenzoic acid is 40-80% by mole, the added amount of 6-acetoxy-2-naphthoic acid is 10-40%, and the added amount of raw material B is 5-30%; when raw material A selects raw material C, the added amount of p-acetoxybenzoic acid is 40-80% by mole, the added amount of 6-acetoxy-2-naphthoic acid is 10-40%, the added amount of aromatic diacid is 5-15%, and the added amount of fluorinated aromatic diacetylamide is 5-15%; further, the molar ratio of aromatic diacid to fluorinated aromatic diacetylamide is 1:
1.
5. The method for preparing a polynaphthyl ester according to any one of claims 1 to 4, characterized in that: The catalyst is selected from one or more of titanium dioxide, titanium glycol, titanium acetylacetonate, n-butyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannic acid, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, and zinc lactate; further, the catalyst is added in an amount of 40 to 450 ppm of the total weight of p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, and raw material A.
6. The method for preparing a polynaphthyl ester according to any one of claims 1 to 5, characterized in that: The antioxidant is selected from one or more of antioxidant BHT, antioxidant 1010, antioxidant 168, triphenyl phosphite, and dilauryl thiodipropionate; further, the added amount of the antioxidant is 0.05-0.5% of the total weight of acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid and raw material A.
7. The method for preparing a polynaphthyl ester according to any one of claims 1 to 6, characterized in that: Satisfy at least one of the following: The reaction is carried out at 200-220° C. for 1.5-3 hours; The reaction is carried out at 240-280° C. for 2-3 hours; The reaction is carried out at 300-360° C. for 0.1-3 hours; The reaction is carried out at 300-340° C. for 5-30 minutes; The vacuum degree of the vacuum is 0.08-0.1MPa; The shear rate is controlled to be 50-200s during the continuous polymerization reaction. -1 .
8. The polynaphthyl ester prepared by the method for preparing the polynaphthyl ester according to any one of claims 1 to 7.
9. The polynaphthyl ester according to claim 8, characterized in that: The structural formula is shown in formula (I): Further, in terms of mole percentage, n1 is 40-80%, n3 is 10-40%, and n2 is 5-30%; Furthermore, in terms of mole percentage, n1 is 45-70%, n3 is 20-40%, and n2 is 10-30%.
10. The polynaphthyl ester according to claim 8, characterized in that: The structural formula is shown in formula (II): Further, in terms of mole percentage, n1 is 40-80%, n2 is 10-40%, the mole percentage of Ar1 is 5-15%, the mole percentage of Ar2 is 5-15%, and the mole percentage of Ar1 is equal to the mole percentage of Ar2; Furthermore, in terms of mole percentage, n1 is 45-70%, n2 is 20-40%, the mole percentage of Ar1 is 2.5-12.5%, the mole percentage of Ar2 is 2.5-12.5%, and the mole percentage of Ar1 is equal to the mole percentage of Ar2.
Citation Information
Patent Citations
High-modulus thermotropic liquid crystal polyarylester film, and preparation method and application thereof
CN113683759A
Preparation method of low-dielectric high-viscosity LCP material
CN113831522A
Preparation method of branched thermally-induced aromatic liquid crystal polyester
CN114106307A
High-performance liquid crystal polyarylate fiber as well as preparation method and production equipment thereof
CN114134590A
Liquid crystal polymer as well as preparation method and application thereof
CN116178689A